The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s12094-022-03034-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicted cardiac and second cancer risks for patients undergoing VMAT for mediastinal Hodgkin lymphoma

Abstract: Background and purpose To predict treatment-related cardiovascular disease (CVD) and second cancer 30-year absolute mortality risks (AMR30) for patients with mediastinal Hodgkin lymphoma in a large multicentre radiation oncology network in Ireland. Material and methods This study includes consecutive patients treated for mediastinal lymphoma using chemotherapy and involved site radiotherapy (RT) 2016–2019. Radiation doses to heart, left ventricle, cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Houlihan et al [32 ▪ ] introduced a method for predicting treatment-related second cancer and absolute mortality risks (AMR 30 ) in patients with mediastinal Hodgkin lymphoma who underwent photon radiation therapy. The research group suggested that planning techniques using volumetric-modulated arc therapy, in combination with deep inspiration breath-hold are linked to reduced doses to the heart, lungs, and breasts.…”
Section: Second Malignancymentioning
confidence: 99%
“…Houlihan et al [32 ▪ ] introduced a method for predicting treatment-related second cancer and absolute mortality risks (AMR 30 ) in patients with mediastinal Hodgkin lymphoma who underwent photon radiation therapy. The research group suggested that planning techniques using volumetric-modulated arc therapy, in combination with deep inspiration breath-hold are linked to reduced doses to the heart, lungs, and breasts.…”
Section: Second Malignancymentioning
confidence: 99%